2002
DOI: 10.1172/jci0214345
|View full text |Cite
|
Sign up to set email alerts
|

Viral induction of a chronic asthma phenotype and genetic segregation from the acute response

Abstract: Paramyxoviral infections cause most of the acute lower respiratory tract illness in infants and young children and predispose to the development of chronic wheezing, but the relationship between these short-and long-term viral effects are uncertain. Here we show that a single paramyxoviral infection of mice (C57BL6/J strain) not only produces acute bronchiolitis, but also triggers a chronic response with airway hyperreactivity and goblet cell hyperplasia lasting at least a year after complete viral clearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 68 publications
5
118
2
2
Order By: Relevance
“…Neutrophilic inflammation is a common inflammatory response associated with the development of goblet cell metaplasia after LPS exposure in mouse lung (65), endotoxin exposure to rat nasal epithelium (47), ozone-exposed rat nasal epithelium (8), combined endotoxin and ozone exposure to rat nasal epithelium (57), or cigarette smoke exposure to mouse lung (33). Importantly, inhibition of neutrophilic inflammation by glucocorticoid treatment (22,58), or anti-neutrophil antiserum (8,47,57), reduces goblet cell metaplasia. Similar to these other models, we suggest that NE-induced inflammation plays an important role in the development of goblet cell metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophilic inflammation is a common inflammatory response associated with the development of goblet cell metaplasia after LPS exposure in mouse lung (65), endotoxin exposure to rat nasal epithelium (47), ozone-exposed rat nasal epithelium (8), combined endotoxin and ozone exposure to rat nasal epithelium (57), or cigarette smoke exposure to mouse lung (33). Importantly, inhibition of neutrophilic inflammation by glucocorticoid treatment (22,58), or anti-neutrophil antiserum (8,47,57), reduces goblet cell metaplasia. Similar to these other models, we suggest that NE-induced inflammation plays an important role in the development of goblet cell metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin induces goblet cell metaplasia in mouse airways (65) and in rat nose (47) and potentiates ozone-induced goblet cell metaplasia (57) in rat nasal epithelium. Infection with paramyxovirus in mice induces a chronic goblet cell metaplasia (58); this response is partially mitigated by glucocorticoid treatment. Environmental toxins can also stimulate secretory cell remodeling, usually associated with an inflammatory response.…”
mentioning
confidence: 99%
“…Mucus production has not been associated with development of AHR in allergeninduced models 33 or in a model in which cytomegalovirus infection is combined with allergen. 34 Walter et al 35 reported on the differences in genetic control of AHR and goblet cell hyperplasia in Sendai virus-infected mice. Furthermore, we have previously shown that mucus hyperproduction per se is not essential to development of AHR after allergen sensitization and challenge.…”
Section: Discussionmentioning
confidence: 99%
“…19 It has generally been thought that IL-13 is primarily produced by T H 2 cells, but many cell types, including mast cells, 15 macrophages, 35 CD8, and T H 1 cells, 17,18 prominent cells in RSV pathology, can produce IL-13. Although IL-13 can aggravate eosinophilic inflammation in allergen-induced models, [10][11][12][13][14] it also might exhibit important anti-inflammatory properties.…”
Section: Park Et Al 1083mentioning
confidence: 99%
“…Relevant to both the immune and pulmonary responses to infection, the stage of development might be a key determinant to the severity of the infection and the eventual pulmonary outcomes. For example, evidence in animal models indicates that infections in early life could cause reprogramming of epithelial cells 28,29 and modify the generation of antiviral T cells 30 to alter immune responses in the airway mucosa. In addition, LRIs during an active period of lung and immune development could adversely affect these processes to cause airway remodeling or to interfere with the generation of new alveoli.…”
Section: The Relationship Of Early Virus-induced Wheezing To Childhoomentioning
confidence: 99%